Effect of i-ZnO seed layer on the properties of electrodeposited p-Cu2O/n-ZnO/FTO heterojunction thin films. (15th November 2019) - Kara, Rania; Rachid, Siab; Azizi, Amor
Abstract: In this study, p-Cu2 O/n-ZnO/i-ZnO/FTO heterojunction have been successfully deposited via a simple three-step electrodeposition method. The effects of inserting ZnO seed layer on the properties of the heterojunctions were investigated using a variety of analysis techniques. Mott-Schottky analysis indicated p-type conductivity for Cu2 O and n-type conductivity for ZnO thin films. X-ray diffraction (XRD) patterns indicated that the ZnO nanostructures were of polycrystalline nature with highly hexagonal ZnO (002) oriented crystallites and cubic structure of Cu2 O having (111) preferential orientations. This was confirmed by field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM) analysis revealed that the Cu2 O/ZnO heterojunctions were composed of hexagonal grains in the underlying layers while the higher layer exhibited typical pyramids features. Also, experimental results pointed out that the insertion of the seed layer could produce denser microstructures, and improve compactness and surface flatness of the thin films. From UV-vis spectra, a blue shift of the bandgap with an obviously increase in the optical transparency to 80% were noted by the insertion of the seeding layer approach. Current-voltages (I-V) plots of Au/p-Cu2 O/n-ZnO/i-ZnO/FTO heterojunctions showed excellent rectifying behavior, and their electrical characteristics can be effectively tuned through the contribution of ZnO seed layer. This study demonstrates the crucial role of seeding layer in the nucleation-growth and consequently in the properties of these heterojunctions.